Typical coastal scenery, Trinidad, B.W.I. - 11 - (:unkn) unknown ([Printed in Germany], 2009)
Beach scene in Trinidad
Colour; Landscape
Keywords: Postcards; Trinidad and Tobago; Beaches; Coastal scenery